1996
DOI: 10.1037/0278-6133.15.3.209
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of the protection motivation theory in explaining hearing protection device use among male industrial workers.

Abstract: The present study examined the usefulness of personal variables: noise annoyance, and components of the protection motivation theory (R. W. Rogers, 1983) along with social-organizational factors in explaining hearing protection device (HPD) use among Israeli manufacturing workers. Participants were 281 men exposed to harmful noise levels for which routine HPD use is required by regulation. In practice, 3 HPD user groups were identified: nonusers (n = 38), occasional users (n = 125), and regular users (n = 118)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
60
0
2

Year Published

1998
1998
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(69 citation statements)
references
References 35 publications
5
60
0
2
Order By: Relevance
“…These findings support the importance of self-efficacy in positively changing health and safety behaviors [Kelly et al, 1991;Melamed et al, 1996;Wulfert and Wan, 1993].…”
Section: Discussionsupporting
confidence: 74%
“…These findings support the importance of self-efficacy in positively changing health and safety behaviors [Kelly et al, 1991;Melamed et al, 1996;Wulfert and Wan, 1993].…”
Section: Discussionsupporting
confidence: 74%
“…Briefly, we adopted a modified version of the HPM (Pender et al, 1990;Pender, 1996) and designed the training program around the original HPM elements of self-efficacy, benefits to prevention, barriers to prevention, interpersonal and situational influences, as well as elements addressing perceived susceptibility and perceived severity (Melamed et al, 1996). In addition, the program addressed specific knowledge about hearing loss prevention Seixas et al Page 4 Int J Audiol.…”
Section: Interventionsmentioning
confidence: 99%
“…Although the HPM has been effectively used to explain and motivate use of HPDs in past studies (Lusk et al, 1994(Lusk et al, , 1999a(Lusk et al, , 1997Ronis et al, 2006), this model does not include risk perceptions around hearing loss due to noise exposure. Melamed and colleagues demonstrated that constructs from other value-expectancy models such as the health belief model also significantly predict HPD use (Melamed et al, 1996). In particular the perceived threats of noise exposure (i.e.…”
mentioning
confidence: 99%
“…Some authors point out barriers about comfort to the use of the protectors (Melamed et al, 1996;Davis et al, 2009;Byrne, 2011). Others research point the relationship between hearing protection use and risk perception in the work environment (Rabinowitz et al, 2007) and indicate that the most effective use of hearing protection in the workplace is more related in places where noise exposure is higher.…”
Section: Hearing Proctetors Usementioning
confidence: 99%